Determination of multiple pesticide residues in teas by gas chromatography with accurate time‐of‐flight mass spectrometry. Issue 11 (10th May 2019) - Li, Jianxun; Teng, Xiaoyu; Wang, Wenwen; Zhang, Zijuan; Fan, Chunlin
Abstract: In this work, gas chromatography tandem with electron ionization and full‐scan high‐resolution mass spectrometry with a time‐of‐flight mass analyzer was evaluated for analyzing pesticide residues in teas. The relevant aspects for mass spectrometry analysis, including the resolution and mass accuracy, acquisition rate, temperature of ion source, were investigated. Under acquisition condition in 2‐GHz extended dynamic range mode, accurate mass spectral library including 184 gas chromatography detectable pesticides was established and retrieval parameters were optimized. The mass spectra were consistent over a wide concentration range (three orders) with good match values to those of NIST (EI‐quadrupole). The methodology was verified by the validation of 184 pesticides in four tea matrices. A wide linear range (1–1000 μg/kg) was obtained for most compounds in four matrices. Limit of detection, limit of quantification, and limit of identification values acquired in this study could satisfy the requirements for maximum residue levels prescribed by the European Community. Recovery studies were performed at three concentrations (10, 50, and 100 μg/kg). Most of the analytes were recovered at an acceptable range of 70–120% with relative standard deviations ≤ 20% in four matrices. The potential extension of qualitative screening scope makes gas chromatography tandem with electron ionization and mass spectrometry with a time‐of‐flight mass analyzer a more powerful tool compared with gas chromatography with tandem mass spectrometry.